Energy service companies in China: The role of social networks and trust - Genia Kostka; Kyoung Shin (Frankfurt School of Finance & Management, 2011)
China's energy-service companies (ESCOs) have developed only modestly despite favorable political and market conditions. We argue that with sophisticated market institutions still evolving in China, trust-based relations between ESCOs and energy customers are essential for successful implementation of energy efficiency projects. Chinese ESCOs, who are predominantly small and private enterprises, perform poorly in terms of trust-building because they are disembedded from local business, social, and political networks. We conclude that in the current institutional setting, the ESCO model based on market relations has serious limitations and is unlikely to lead to large-scale implementation of energy efficiency projects in China.
Keywords: Q40; Q48; O53; 330; energy policies; energy service companies (ESCO); social networks; trust; China; Energiewirtschaft; Dienstleistungssektor; Energiesparen; Soziales Netzwerk; China